Women and Terrorism: A Sketch on Women and Transnational Terrorism in Southeast Asia and Indonesia - Herdi Sahrasad; Dedy Tabrani; Muhammad Ridwan; Al Chaidar (Budapest International Research and Critics University, 2020)
In Southeast Asia, many women in radical groups have extreme views and they are ready to join Jihadist movement to support her husband's actions as Jihad fi sabilillah. In this context, experience in Southeast Asia shows the increasing involvement of women in terrorism by reason of following the husband's jihad to fight thogut regimes in the region. Meanwhile, there are a large number of Islamic terrorist organizations involving active women throughout the Southeast Asian region, from Thailand, Malaysia, Indonesia, Singapore to the Philippines. In this regard, the emergence of ISIS has strengthened and institutionalized acts of terror and violence by Southeast Asian women following the ISIS declaration to establish a regional khilafah (Caliphate).